Are the guidelines concerning the prescription of biotherapy respected? Enquiry in an internal medicine department at Bordeaux University Hospital. Issue 2 (12th March 2012) - Herrador, C.; Lanta, C.; Dieval, C.; Duffau, P.; Ribeiro, E.; Pometan, J.P.; Pedeboscq, S.; Mercie, P.; Longy-Boursier, M.
Abstract : Background: Numerous biotherapies have been developed these previous years and have enhanced the prognosis of inflammatory diseases and cancers. Most of these molecules are onerous and clinicians must follow prescription guidelines. Purpose: The objective of this study is to evaluate the adequation of biotherapy prescriptions with edited guidelines and analyse off-label situations. Materials and methods: A prospective study was performed concerning patients treated by biotherapy from November 2010 to June 2011 in an internal medicine department. The following data were collected: indication, previous treatments, clinical and scientific relevance. Results: 76 patients were included receiving rituximab (37/76), infliximab (27/76), anakinra (4/76), adalimumab (3/76), eculizumab (1/76), tocilizumab (1/76), etanercept (1/76), alemtuzumab (1/76), bevacizumab (1/76). 62/76 indications were correctly specified; (a pharmacist corrected 14 errors). 57/76 prescriptions respected the guidelines. The 19 off label situations were: rituximab (9/37), anakinra (4/4), infliximab (2/27), adalimumab (2/3), tocilizumab (1/1), bevacizumab (1/1). These molecules were used as a third-line and over for 14 patients, second-line (3 patients), first-line (2 patients). These drugs were prescribed because classical therapies were ineffective, not well tolerated or contraindicated. Only 3 prescriptions were justified by scientific publications. One case was discussed in clinical pluridisciplinary comity of haematology. Biotherapy treatment was pursued with good efficacy for 13 patients: 11 had good tolerance and recurrent infections were recorded for 2 patients. The treatment was ceased for 1 patient because of it inefficacy. Efficacy evaluation was not possible for 5 patients: lack of experience (1), reserved prognosis when biotherapy started (3); 1 lost to follow-up patient. Conclusions: This study proved that most of off-label biotherapy prescriptions are used when classical therapies are not effective or contraindicated and have enhanced the prognosis for the great majority of patients. Nevertheless, physicians do not justify these prescriptions as recommended in France. Consequently a clinical pluridisciplinary comity of internal medicine was created to improve the therapeutic justification and decision and pharmacy elaborated documents to inform prescribers concerning the rules for off-label situations.